2015
DOI: 10.1016/j.jenvman.2014.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Fragmented local governance and water resource management outcomes

Abstract: Abstract:Fragmented jurisdictions and decision making structures can result in destructive competition and/or a lack of systematic cooperation that can hamper effective resource management and environmental planning, although the value of local autonomy and stakeholder participations should not be underestimated. This study empirically examines if political fragmentation in local governance is a significant barrier to successful resource management. To test this hypothesis, the authors quantify the degree of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 41 publications
2
27
0
Order By: Relevance
“…Fragmented water service provision creates opportunities for flexibility, responsiveness, and services well‐ tailored to local populations (Swyngedouw, Kaïka, & Castro, ), but can also result in disparate local outcomes (Kim et al, ; Mullin, ; Scott et al, ). Moreover, independent providers face regional collective action challenges (Feiock, ), such as how shared environmental (Kim et al, ) and economic (Berry, ) resources are allocated. The EoG framework (Lubell, ) has emerged as a way to understand how network structures form and evolve as policy actors pursue their aims within polycentric governance systems.…”
Section: Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…Fragmented water service provision creates opportunities for flexibility, responsiveness, and services well‐ tailored to local populations (Swyngedouw, Kaïka, & Castro, ), but can also result in disparate local outcomes (Kim et al, ; Mullin, ; Scott et al, ). Moreover, independent providers face regional collective action challenges (Feiock, ), such as how shared environmental (Kim et al, ) and economic (Berry, ) resources are allocated. The EoG framework (Lubell, ) has emerged as a way to understand how network structures form and evolve as policy actors pursue their aims within polycentric governance systems.…”
Section: Rationalementioning
confidence: 99%
“…This fragmentation of local governance responsibilities poses an array of regional coordination challenges (Feiock, ), complicating both the production of public goods (Oakerson & Parks, ) and the management of common pool resources (Berry, ) by increasing the number of independent organizations involved. One prominent example of fragmentation and its ensuing challenges is with regional drinking water provision (Kim, Keane, & Bernard, ; Scott, Moldogaziev, & Greer, ; Teodoro & Switzer, ).…”
Section: Introductionmentioning
confidence: 99%
“…but in reality, the city-scale imposes immense pressure on ecology and infrastructure with added complications such as fragmented societies, higher inequality, and rising informality [4,5]. Megacities, characterized by numerous decision-making authorities, often struggle to achieve collaboration in solving urban sprawl, land use conversion, and water management problems [6].The rapid process of urbanization in megacities is causing environmental, economic, and social problems. Development has been accompanied by negative consequences for many river systems, including changes in their hydrology and ecology.…”
mentioning
confidence: 99%
“…Through pursuing socio-economic objectives of rural communities, the approach facilitates linkages between water resource conservation and community livelihood enhancement [8,9]. For instance, evidence was found in a variety of settings that community engagement improves sustainability of water supply systems [6,8,[10][11][12][13], water quality improvement [14], conflict management [15], and other social outcomes [16]. Kativhu et al [10] observed that the sustainability of water supply facilities could be improved through building stronger capacities in technical, social, and institutional aspects.…”
mentioning
confidence: 99%
“…Moreover, the willingness to participate in community-based water resource management is affected by many contextual variables including the sense of community, dependency on and concerns for water resources, social trust, perceptions of organizational support, incentives, and information sources [11,13,16,18,19]. Similarly, stakeholder participation and collaboration in water resource management is influenced by political fragmentation [14], resource boundary and payment rules [17], and state and local water policies and regulations [6,20,21]. These policies regulating common-pool resources management were evaluated using the Institutional Analysis and Development (IAD) framework [22][23][24][25].…”
mentioning
confidence: 99%